Varietal evaluation of black pepper (Piper nigrum L.) for yield, quality and anthracnose disease resistance in Idukki District, Kerala - Josephrajkumar, M Murugan, P Sainamole Kurian, S Backiyarani, A (Journal of Spices and Aromatic Crops, 2002)
Fourteen accessions of black pepper were evaluated at the Cardamom Research Station, Pampadumpara for yield, quality and disease resistance. Out of the fourteen cultivars, CuI. 239 (Panniyur-5) recorded the highest wet (906.5 g) and dry (310.1 g) yield of berries per plant. The maximum volatile oil (5.06%) and oleoresin (9.4%) contents in dry berries were observed in CuI. 5128 and Panniyur-1, respectively. A positive correlation existed between the number of spikes and berries per plant and yield. However, yield and quality characters are negatively correlated, though not significant. The results showed that Panniyur-5 is the most suitable black pepper variety for high range conditions of Idukki District.